GASTRONOMIC CULTURE AS A BRIDGE BETWEEN TRADITIONS OF THE WORLD'S PEOPLES AND SELF-KNOWLEDGEMENT (TO THE QUESTION OF MULTICULTURALISM IN E. GILBERT'S NOVEL "EAT. PRAY. LOVE". - Terekhovska, Olena; Maksymiv, Tetyana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
Annotation. The article examines gastronomic culture as a space for the spiritual unity of different cultures, traditions, and mentalities in E. Gilbert’s novel «Eat, Pray, Love». It is demonstrated that food represents a unique dimension where individual corporeality intersects with collective memory, and where new forms of communication and identity are formed. Food is shown to serve as a symbolic bridge between a person and cultural heritage, between different peoples, and between an individual and their inner self. The study argues that “Eat,” as a symbol and key to self-discovery, reflects various aspects of human life: economy, history, symbolism, shared heritage, and personal experience. It is revealed that gastronomic culture – through taste experiences, the tradition of hospitality, and the affirmation of the pleasure in “doing nothing” – acts as a bridge for mutual understanding that can restore a sense of happiness and spiritual wholeness. The novel portrays gastronomy as a multicultural phenomenon and a means of cultural and spiritual interethnic integration, underscoring its multicultural essence and philosophy.